INTEGRATING AI-POWERED LANGUAGE MODELS IN ESL CLASSROOMS: STRATEGIES FOR EFFECTIVE TEACHING - Gulruh Furqat qizi Bozorova (Web of Journals Publishing, 2025)
Nowadays artificial intelligence is becoming one of the most used parts all over the world. Clearly, we can see AI-powered language models, like ChatGPT, the way English is taught and learned in all classrooms of ESL. These advanced technologies, besides modern gadgets can interpret and generate natural language. By using from these modern technologies most of the teacher and students can increase their knowledge in education process. In the field of education, AI tools could support nearly all of the sections like lesson planning, reduce grading workload, and offer creative solutions for language educators. During the language learning process particularly, they can provide input, generate interactive dialogues, and get tailored feedback to individual student needs. In this article we can explore how AI-powered language models can be effectively integrated into the ESL classroom to enhance engagement, generate personalized learning, and increase teaching proficiency.
Keywords: Artificial Intelligence, Language Models, ESL Teaching, Educational Technology, ChatGPT, Personalized Learning, Language Instruction, Classroom Strategies.